Implementation of Competency-Based Career Management in Improving the Professionalism of Medical Personnel at Islamic Hospital Banjarmasin - Puspa Widiyawati; Rinawati Rinawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
In facing the challenges of an increasingly complex and dynamic world of work, competency-based career management is a strategic approach in managing human resources, especially medical personnel. This study aims to examine the implementation of competency-based career management system in improving the professionalism of medical personnel in Banjarmasin Islamic Hospital. Using descriptive qualitative methods based on literature studies, this study highlights the importance of structuring career paths that are structured and oriented to technical and non-technical competencies, such as communication skills, leadership, and ethical integrity. The results of the analysis show that this approach is not only able to answer the internal needs of the hospital in building a professional work culture, but also a strategic response to the demands of quality health services, fast, and humane. The implications of this implementation are expected to encourage increased work motivation, service efficiency, and competitiveness of health institutions in the modern era.